Machining feasibility and sustainability study on end milling process of Monel alloy. (2021) - Shihan, Muhammed; Chandradass, J.; Kannan, T.T.M.; Sivagami, S.M.
Abstract: Minimizing the resource consumption and reducing the manufacturing system's environmental impact has been increased in today's manufacturing trend. The proposed study deals with the sustainability of the machining process of Monel (K-400) in the End milling process. Spindle speed feed and depth of cut are process parameters of the milling process and are set as four levels. Surface roughness, MRR, Tool wear, tool life, and energy consumption were considered as sustainability factors. The result revealed that factors such as Lower surface roughness (1.26 µm), Minimum tool wear (0.2 mm), Maximum tool life (8, 79, 200 min), Maximum material removal rate (32 mm 3 /s) increased the sustainability of the end milling process of Monel material.